Solar cell, preparation method thereof and photovoltaic module
Through laser sintering technology, the gate line sintering temperature is optimized on the light-to-light side and backlight side of the solar cell, which solves the problem that the optimal sintering process cannot be met at the same time in the prior art, and achieves the performance improvement of high and low temperature hybrid batteries.
Patent Information
- Application Number
- CN202411514055.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-08-22
AI Technical Summary
During the high-temperature sintering process of existing solar cells, the gate lines toward the light side and backlight side cannot meet the optimal sintering process at the same time, resulting in poor contact effect and high contact resistivity.
Laser sintering technology is used to process the light-to-light side and backlight side of the solar cell respectively. By adjusting parameters such as laser power, the gate line sintering temperature on each side is optimal, forming a high and low temperature hybrid battery, taking into account the performance optimization of both sides.
The performance of solar cells is improved, especially the contact effect and contact resistivity, and the overall performance and photoelectric conversion efficiency of the battery are improved.
Smart Images

Figure CN120529671A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic technology, in particular to a solar cell and a preparation method thereof, and a photovoltaic module. Background Art
[0002] The grid lines in solar cells are used to collect and conduct current. In current solar cells, a sintering furnace is generally used to perform high-temperature sintering to form the grid lines.
[0003] In the case where grid lines are provided on both the light-facing side and the backlight side, in order to simplify the process, a conventional sintering furnace completes the metallization of the light-facing side and the backlight side through one sintering.
[0004] However, during the high-temperature sintering process, the temperature reaches as high as 800°C to 900°C. After passing through the sintering furnace, the film layers formed at high temperature before sintering the grid lines and the film layers formed at low temperature will be subjected to high temperature indiscriminately. As a result, the film layers formed at low temperature will be affected by the heat of sintering, affecting the performance of the solar cell. In addition, due to the different film layer structures on the light-facing side and the backlight side, the optimal sintering temperature points required for the grid lines on the light-facing side and the backlight side are different. Complete the metallization of the light-facing side and the backlight side through a single sintering process, and it is impossible to simultaneously meet the requirements of using the optimal sintering process for both the light-facing side and the backlight side. This results in poor grid line contact and high contact resistivity, which also affects the performance of the solar cell. Summary of the Invention
[0005] The present invention provides a solar cell and a preparation method thereof, and a photovoltaic module, aiming to solve the problems of poor cell performance and high contact resistivity caused by using a sintering furnace to prepare grid lines in existing solar cells.
[0006] A first aspect of the present invention provides a method for preparing a solar cell, comprising:
[0007] Providing a silicon substrate, the silicon substrate comprising: a first surface and a second surface opposite to each other;
[0008] forming a first semiconductor layer on the first surface; the first semiconductor layer undergoes a first temperature treatment;
[0009] A second semiconductor layer is formed on the second surface; the second semiconductor layer is treated at a second temperature; the first temperature is greater than the second temperature; the first semiconductor layer and the second semiconductor layer have different doping types;
[0010] Printing a first electrode paste on the first semiconductor layer to obtain a first gate line precursor, and printing a second electrode paste on the second semiconductor layer to obtain a second gate line precursor;
[0011] Laser sintering is performed on the first grid line precursor to obtain the first grid line.
[0012] In the present application, the first semiconductor layer has been subjected to a first temperature treatment, and the second semiconductor layer has been subjected to a second temperature treatment, the first temperature being greater than the second temperature, and compared to the first semiconductor layer, the first semiconductor layer is a high-temperature film layer and the second semiconductor layer is a low-temperature film layer, that is, the solar cell is a high-low temperature hybrid cell, which has the advantages of both high-low temperature films and good performance. Moreover, in the process of obtaining the first grid line by laser sintering, only the first grid line precursor and the structure near it will be affected by the laser, and the second semiconductor layer will basically not be affected by the heat of the laser sintering, and then in the process of forming the first grid line by laser sintering, the second semiconductor layer will basically maintain its original characteristics, thereby ensuring the performance of the second semiconductor layer and improving the performance of the solar cell. In addition, the first surface side adopts laser sintering to obtain the first grid line, and by adjusting parameters such as laser power, the temperature of the laser sintering is easy to meet the optimal sintering temperature of the first electrode slurry, so that the sintering temperature of the first grid line precursor on the first surface side is the optimal sintering temperature point, so that the contact effect of the first grid line on the first surface side is better, the contact resistivity is low, etc., further improving the performance of the solar cell. At the same time, by laser sintering the first grid line precursor, the curing processes of the first grid line precursor and the second grid line precursor can not interfere with each other, and the setting temperature of the grid lines on the first surface side and the second surface side of the solar cell can be taken into account, so that the sintering temperature of the first surface side and the second surface side are both the optimal sintering temperature points, that is, the best sintering process can be used on both the first surface side and the second surface side, so that the contact effect of the grid lines on the first surface side and the second surface side is better, the contact resistivity is low, etc., further improving the performance of the solar cell.
[0013] Optionally, before laser sintering, the method further comprises:
[0014] The first gate line precursor and the second gate line precursor are cured.
[0015] Optionally, the curing temperature is 150°C to 300°C.
[0016] Optionally, in the direction of the line width of the first gate line precursor, the size of the laser spot is greater than or equal to the line width of the first gate line precursor, and less than or equal to 120% of the line width of the first gate line precursor.
[0017] Optionally, the first electrode paste is aluminum grid line paste, and the laser power used for sintering is a first power; the first electrode paste is silver grid line paste, and the laser power used for sintering is a second power; the second power is greater than or equal to the first power.
[0018] Optionally, the second power is 10W-1000W; the first power is 5W-900W.
[0019] Optionally, the first electrode slurry contains black dye; the mass proportion of the black dye in the first electrode slurry is 0.5% to 2%.
[0020] Optionally, forming a first semiconductor layer on the first surface includes:
[0021] forming an entire first semiconductor layer on the first surface;
[0022] The first semiconductor is patterned so that the first semiconductor layer partially covers the first surface.
[0023] A second aspect of the present invention provides a solar cell, comprising:
[0024] A silicon substrate, comprising: a first surface and a second surface opposite to each other;
[0025] a first semiconductor layer located on the first surface; the first semiconductor layer comprises a polysilicon layer;
[0026] a second semiconductor layer located on the second surface; the second semiconductor layer comprises at least one of amorphous silicon, microcrystalline silicon, and nanocrystalline silicon; the first semiconductor layer and the second semiconductor layer have different doping types;
[0027] a first gate line, located on the first semiconductor layer; a metal-crystalline silicon alloy is formed between the first gate line and the first semiconductor layer;
[0028] The second gate line is located on the second semiconductor layer.
[0029] Optionally, a maximum size of a hole in a cross section of the first gate line is less than or equal to 2 micrometers.
[0030] Optionally, in the first gate line, the reflectivity of the surface facing away from the first semiconductor layer is less than or equal to 10%.
[0031] Optionally, the line width of the first gate line is smaller than the line width of the second gate line.
[0032] Optionally, the porosity of the first grid lines is smaller than the porosity of the second grid lines.
[0033] Optionally, the first grid line contains glass powder and black dye; the black dye further contains a colorant;
[0034] The mass proportion of the color body in the black dye is 10% to 60%.
[0035] Optionally, the first semiconductor layer includes: a tunneling oxide layer and a doped polysilicon layer stacked together, wherein the tunneling oxide layer is closer to the silicon substrate;
[0036] The second semiconductor layer includes: an intrinsic amorphous silicon layer and a doped amorphous silicon layer that are stacked, wherein the intrinsic amorphous silicon layer is closer to the silicon substrate; and the doping type of the doped polysilicon layer is different from the doping type of the doped amorphous silicon layer.
[0037] Optionally, the solar cell further includes: a transparent conductive layer located between the second semiconductor layer and the second grid line; and / or,
[0038] The first semiconductor layer partially covers the first surface; and / or,
[0039] The solar cell further includes a passivation anti-reflection film covering the first surface and the first semiconductor layer.
[0040] A third aspect of the present invention provides a photovoltaic module, comprising: a solar cell prepared by any of the aforementioned methods for preparing a solar cell, and / or a solar cell as described in any of the aforementioned methods.
[0041] The above-mentioned solar cells and preparation methods thereof and photovoltaic modules have the same or similar beneficial effects, and are not described in detail here to avoid repetition. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0043] Figure 1 A schematic diagram of laser sintering in an embodiment of the present invention is shown;
[0044] Figure 2 A partial SEM schematic diagram of a first grid line of a solar cell according to an embodiment of the present invention is shown;
[0045] Figure 3 A partial SEM schematic diagram of the first grid line of a solar cell of a comparative example is shown.
[0046] Description of the accompanying figures:
[0047] 11-Laser, 12-First grid line precursor, 13-Second grid line. DETAILED DESCRIPTION
[0048] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.
[0049] The present invention provides a method for preparing a solar cell, comprising the following steps.
[0050] Step 101: Provide a silicon substrate, wherein the silicon substrate comprises a first surface and a second surface opposite to each other.
[0051] One of the first surface and the second surface is a light-facing surface, and the other is a backlight surface. During normal operation of the battery, the surface of the silicon substrate that mainly receives light is the light-facing surface, and the backlight surface is opposite to the light-facing surface.
[0052] Step 102: forming a first semiconductor layer on the first surface; the first semiconductor layer undergoes a first temperature treatment.
[0053] The first semiconductor layer can be formed on the first surface of the silicon substrate by low pressure chemical vapor deposition (LPCVD) or other methods. During the formation of the first semiconductor layer, the first semiconductor undergoes a first temperature treatment. The specific method for forming the first semiconductor layer is not specifically limited.
[0054] Optionally, the first semiconductor layer may include: a stacked tunneling oxide layer and a doped polysilicon layer, wherein the tunneling oxide layer is closer to the first surface of the silicon substrate, thereby forming a passivation contact structure, which can provide excellent surface passivation and good selective collection of carriers, thereby improving the conversion efficiency of the battery.
[0055] Optionally, step 102 may also include: forming an entire first semiconductor layer on the first surface, and patterning the entire first semiconductor layer so that the first semiconductor layer partially covers the first surface. The patterning here can be formed with the aid of a mask, for example, forming a local mask layer on the first semiconductor layer, and patterning the first semiconductor layer under the protection of the mask layer to form a local contact structure, which not only reduces the light absorption loss of the first surface and maintains a low contact recombination, but also the subsequent first gate line precursor is only formed on the local first semiconductor layer, and the subsequent laser has basically no adverse effect on the non-contact area on the side of the first surface, and basically has no adverse effect on the passivation film layer in the non-contact area, so that the passivation quality of the non-contact area is better, further improving the photoelectric conversion efficiency of the solar cell.
[0056] Step 103 , forming a second semiconductor layer on the second surface; the second semiconductor layer is subjected to a second temperature treatment; the first temperature is greater than the second temperature; the first semiconductor layer and the second semiconductor layer have different doping types.
[0057] A second semiconductor layer can be formed on the second surface of the silicon substrate by plasma vapor deposition or other methods. During the formation of the second semiconductor layer, the second semiconductor layer undergoes a second temperature treatment. There is no specific limitation on the specific formation method of the second semiconductor layer. If the first temperature here is greater than the second temperature, then of the first semiconductor layer and the second semiconductor layer, the first semiconductor layer is a high-temperature film layer, and the second semiconductor layer is a low-temperature film layer. The low-temperature film layer is not resistant to high temperatures. If the low-temperature film layer is subjected to high-temperature treatment, it will lose some of its performance, affecting the conversion efficiency of the battery. The second semiconductor layer and the first semiconductor layer here have different doping types, one is N-type doped and the other is P-type doped. This solar cell is a double-sided high and low temperature hybrid cell, which has the advantages of both high and low temperature film layers, has a higher short-circuit current and open-circuit voltage, and has good performance.
[0058] Optionally, the second semiconductor layer may include a stacked intrinsic amorphous silicon layer and a doped amorphous silicon layer. The intrinsic amorphous silicon layer is closer to the second surface of the silicon substrate, effectively passivating surface defects and reducing recombination, thereby improving the conversion efficiency of the battery. The doped amorphous silicon layer and the doped polycrystalline silicon layer have different doping types: one is N-type doped and the other is P-type doped.
[0059] Step 104 : Printing a first electrode paste on the first semiconductor layer to obtain a first gate line precursor, and printing a second electrode paste on the second semiconductor layer to obtain a second gate line precursor.
[0060] A first electrode paste can be applied to the first semiconductor layer using methods such as screen printing to obtain a plurality of first gateline precursors. Laser sintering of one first gateline precursor yields a first gateline. Similarly, a second electrode paste can be applied to the second semiconductor layer using methods such as screen printing to obtain a plurality of second gateline precursors. Curing of one second gateline precursor yields a second gateline.
[0061] Optionally, before step 104, the method may further include: forming a transparent conductive layer on the second semiconductor layer, the second gridline precursor being disposed on the transparent conductive layer, the transparent conductive layer being more compatible with the low-temperature sintered second electrode paste, thereby improving current collection capability and further enhancing solar cell performance. In other words, the solar cell further includes: a transparent conductive layer positioned between the second semiconductor layer and the second gridline to improve current collection capability.
[0062] Step 105 : laser sintering the first gate line precursor to obtain a first gate line.
[0063] The laser can be a continuous infrared laser, etc. By adjusting the laser power, sintering times, etc., it is easy to achieve the best sintering process for the first grid line precursor, thereby obtaining a first grid line of better quality, forming a good electrical contact, and improving the performance of the solar cell.
[0064] Specifically, during the laser sintering process, the heat absorbed from the laser can reach the melting temperature point required to form the metal silicon alloy point, and the passivation anti-reflection material that may exist between the first semiconductor layer and the first grid line precursor will be burned through during the laser sintering process, and a metal silicon crystal alloy will be formed between the first grid line and the aforementioned first semiconductor layer, forming a good electrical contact, thereby improving the performance of the solar cell. On the one hand, laser sintering can mainly act on the first surface side, and has basically no high temperature effect on the low-temperature film layer on the second surface side, so that the second semiconductor layer can basically maintain its original performance, which can improve the conversion efficiency of the solar cell. In addition, the first grid line is obtained by laser sintering on the first surface side, and by adjusting parameters such as laser power, the temperature of the laser sintering is easy to meet the optimal sintering temperature of the first electrode slurry, so that the sintering temperature of the first grid line precursor on the first surface side is the optimal sintering temperature point, the contact effect of the first grid line on the first surface side is better, the contact resistivity is low, etc., further improving the performance of the solar cell. At the same time, by laser sintering the first grid line precursor, the curing processes of the first grid line precursor and the second grid line precursor can not interfere with each other, and the sintering temperature of the grid lines on the first surface side and the second surface side of the solar cell can be taken into account, so that the sintering temperature of the first surface side and the second surface side are both the optimal sintering temperature points, that is, the best sintering process can be used on both the first surface side and the second surface side at the same time, so that the contact effect of the grid lines on the first surface side and the second surface side is better, the contact resistivity is low, etc., further improving the performance of the solar cell.
[0065] Compared with the laser-assisted sintering in the prior art, the laser sintering of the present application enables the first gate line precursor to burn through the passivation anti-reflection material that may exist between the semiconductor layer and the gate line, forming an alloy with silicon and forming a good ohmic contact, which has higher requirements on laser power, etc.; laser-assisted sintering must match the deflection voltage and perform laser scanning on the electrode surface that has formed ohmic contact, thereby further increasing the ohmic contact of the electrode and reducing the contact resistance, which has lower requirements on laser power, etc.
[0066] The first grid lines are used to collect and output current. There is no specific limit on the number of first grid lines in a solar cell.
[0067] Optionally, several first grid lines of the solar cell contain black dye, which contains aromatic sodium sulfonate. The black dye containing aromatic sodium sulfonate has weak reflection of laser and can fully absorb the energy of laser, so that the heat absorbed from the laser can easily reach the melting temperature required to form metal silicon alloy points, and can easily burn through the passivation anti-reflection material that may exist between the first semiconductor layer and the first grid line precursor. Therefore, in the process of forming the first grid line, a better first grid line can be easily prepared by laser sintering.
[0068] It should be noted that, in addition to the black dye, the first gate line may also contain a metal material with good electrical conductivity, etc., which can form a high-quality metal-silicon alloy with the first semiconductor layer on the one hand, and maintain the good electrical conductivity of the first gate line on the other hand. The remaining components of the first gate line are not specifically limited. The black dye in the first gate line can be detected using an energy dispersive spectrometer (EDS), etc., and the specific detection method is not limited.
[0069] Optionally, the first grid line is an aluminum grid line or a silver grid line. The specific grid line can be selected according to specific needs, and the application scenarios are flexible and diverse. An energy spectrometer can also be used to detect whether the first grid line is an aluminum grid line or a silver grid line. The specific detection method is not limited.
[0070] Optionally, in the first grid line, the mass proportion of the black dye is 0.1% to 1%. The mass proportion of the black dye in the first grid line is relatively appropriate, not only will it not affect the conductive properties of the first grid line, but it will also fully absorb the laser heat. In addition, it will not affect the performance of the low-temperature film layer on the back. More specifically, if the mass proportion of the black dye in the first grid line is greater than 1%, it may affect the conductive performance parameters of the first grid line. If the mass proportion of the black dye in the first grid line is less than 0.1%, it may not fully absorb the laser heat during the formation of the first grid line. An energy spectrometer or the like can be used to detect the mass proportion of the black dye in the first grid line, and the specific detection method is not limited.
[0071] For example, in the first grid line, the mass proportion of the black dye can be 0.1%, 0.3%, 0.5%, 0.63%, 0.79%, 0.8%, 0.9%, 0.2%, 0.4%, 0.6%, 0.7%, 0.9%, 0.55%, or 1%.
[0072] Optionally, the black dye may also contain a chromophore, which primarily refers to an unsaturated group capable of absorbing light radiation and exhibiting transitions, and its associated chemical bonds. The addition of this chromophore can further reduce laser reflection and increase the energy absorbed by the laser, allowing the heat absorbed from the laser to fully reach the melting point required to form the metal-silicon alloy. The chromophore in the first grid line can be detected using an energy spectrometer, for example, and the specific detection method is not limited.
[0073] Optionally, the chromophore in the black dye may include at least one of azo, anthraquinone triarylmethane, azine, xanthanone, indigo, quinoline, phthalocyanine, and nitroimide. Chromophores of these compositions exhibit lower laser reflectivity, further increasing laser absorption energy, and are readily available. The specific composition of the chromophore in the grid lines can be detected using an energy dispersive spectrometer, and the specific detection method is not limited.
[0074] Optionally, the weight percentage of the chromophore in the black dye is 10% to 60%. This weight percentage of the chromophore in the black dye is suitable, achieving a good balance between laser reflection and cost. The weight percentage of the chromophore in the black dye in the first grid line can be detected using an energy dispersive spectrometer, etc., and the specific detection method is not limited.
[0075] For example, the mass proportion of the chromophore in the black dye may be 10%, 15%, 25%, 20%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%.
[0076] Optionally, the maximum size of a hole in the cross section of the first grid line is less than or equal to 2 microns. Specifically, since the first grid line utilizes the energy of the laser more concentratedly and is sintered more fully during the formation of the first grid line by laser, the size of the hole after the first electrode slurry is melted is smaller, and the number of holes is less, the melting effect of the first electrode slurry is better, and the conductivity is better. The cross section of the first grid line refers to at least one of the longitudinal section, cross section and oblique section of the first grid line. The longitudinal section of the first grid line is parallel to the thickness direction of the solar cell, the cross section is perpendicular to the thickness direction of the solar cell, and the oblique section is the remaining section except the cross section and the longitudinal section. In the case where there are multiple holes in the same cross section, the maximum size is selected from all the maximum sizes of all the holes in the cross section, and the selected maximum size is less than or equal to 2 microns.
[0077] More specifically, the maximum size of a hole in the cross-section of a grid line formed by sintering in a sintering furnace is typically about 5 microns. The large size and number of holes result in poor electrical connection between the grid line and the first semiconductor layer, and poor electrical conductivity. In this application, laser sintering improves the melting effect of the first electrode slurry, resulting in a better electrical connection between the first grid line and the first semiconductor layer, and better electrical conductivity. Furthermore, in the subsequent formation of a battery string, due to the small size and small number of holes in the first grid line of this application, the electrical connection between the first grid line and the conductive interconnect, such as a soldering ribbon, is more reliable and secure, further improving the electrical performance of the resulting battery string and photovoltaic module.
[0078] For example, the maximum size of a hole in the cross section of the first gate line can be 2 microns, 1.9 microns, 1.7 microns, 1.5 microns, 1.2 microns, 1.3 microns, 1 micron, 0.8 microns, 0.5 microns, 0.4 microns, 0.2 microns, 0.1 micron, 20 nanometers, 40 nanometers, or 50 nanometers.
[0079] Optionally, the reflectivity of the first gridlines facing away from the first semiconductor layer is less than or equal to 10%. The lower reflectivity of the first gridlines results in a darker color for the first gridlines of the solar cell, which enhances the appearance of the solar cell. This is primarily because the addition of the black dye reduces light reflection from the first gridlines, thereby increasing light absorption.
[0080] For example, in the first gate line, the reflectivity of the surface facing away from the first semiconductor layer may be 10%, 9%, 8%, 7%, 6%, 5.5%, 4%, 3%, 2%, or 1%.
[0081] Optionally, the first gate line further contains glass powder, the main component of which is silicon oxide, which has a corrosive effect during the sintering process.
[0082] Optionally, in the aforementioned step 105, the higher the mass proportion of glass powder in the first gate line precursor or the first electrode paste, the lower the power of the laser used for sintering. Specifically, the higher the mass proportion of glass powder, the better the corrosion effect, so the laser power can be appropriately reduced.
[0083] It should be noted that, in the present application, there is no limitation on the specific type of solar cell. For example, the solar cell may be a tunneling oxide contact (TOPCon) solar cell, a hybrid cell, etc.
[0084] Optionally, in the first electrode slurry, the mass proportion of the black dye is 0.5% to 2%. The mass proportion of the black dye in the first electrode slurry is relatively appropriate, not only will it not affect the conductive properties of the first grid line formed subsequently, but also the first electrode slurry absorbs the laser heat more fully. More specifically, if the mass proportion of the black dye in the first electrode slurry is greater than 2%, it may affect the conductive performance parameters of the first grid line formed subsequently. If the mass proportion of the black dye in the first electrode slurry is less than 0.5%, it may not absorb the laser heat sufficiently during the formation of the first grid line. The mass proportion of the black dye in the first electrode slurry can be detected by using an energy spectrometer, etc., and the specific detection method is not limited. It should be noted that during the laser sintering of the first grid line precursor, part of the material in the black dye may volatilize. Therefore, in the formed first grid line, the mass proportion of the black dye will drop slightly to 0.1% to 1%.
[0085] For example, in the first electrode paste, the mass proportion of the black dye can be 0.5%, 0.8%, 0.9%, 1%, 1.05%, 1.1%, 1.2%, 1.5%, 1.7%, 1.6%, 1.8%, 1.9%, or 2%.
[0086] Optionally, the black dye also contains a chromophore. Adding this chromophore to the first electrode paste can further reduce laser reflection and increase laser energy absorption, allowing the first electrode paste to absorb sufficient heat from the laser to reach the melting point required to form metal-silicon alloy dots. The chromophore in the first electrode paste can be detected using an energy dispersive spectrometer, for example, and the specific detection method is not limited.
[0087] Optionally, the weight percentage of the chromophore in the black dye in the first electrode paste is 10% to 60%. This weight percentage of the chromophore in the black dye is suitable, achieving a good balance between laser reflection and cost. The weight percentage of the chromophore in the black dye in the first electrode paste can be detected using an energy dispersive spectrometer, etc., and the specific detection method is not limited.
[0088] For example, the mass proportion of the chromophore in the black dye in the first electrode paste can be 10%, 15%, 25%, 20%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%.
[0089] Yes, in the aforementioned step 105, infrared laser can be used for laser sintering. The heat of infrared laser is more appropriate, and the infrared thermal effect sintering effect is better, which can fully sinter the first electrode paste or the first gate line precursor. Continuous laser can be used to ensure that all positions of the first electrode paste or the first gate line precursor can be sintered, which can avoid sintering omissions in certain positions of the first electrode paste or the first gate line precursor.
[0090] Optionally, in step 105, in the direction of the line width of the first grid line precursor, the size of the laser spot is greater than or equal to the line width of the first grid line precursor and less than or equal to 120% of the line width of the first grid line precursor. That is to say, in the direction of the line width of the first grid line precursor, the laser spot fully covers the first grid line precursor, avoiding sintering omissions caused by too small a spot size. At the same time, the size of the laser spot is not too large, minimizing the laser thermal impact on the non-metallic contact area.
[0091] For example, in the direction of the line width of the first gate line precursor, the size of the laser spot can be the line width of the first gate line precursor, 101% of the line width, 106% of the line width, 105% of the line width, 109% of the line width, 110% of the line width, 111% of the line width, 112.5% of the line width, 115% of the line width, 117% of the line width, 119% of the line width, or 120% of the line width.
[0092] Optionally, in step 105, for a solar cell, the laser scanning time used for laser sintering the first grid line precursor thereon is 0.5s to 5s. On the one hand, the first grid line precursor is sintered more fully within the laser scanning time, and the quality of the obtained first grid line is better. On the other hand, the sintering time is not too long to avoid introducing excessive heat effects.
[0093] For example, for a solar cell, the laser scanning time used for laser sintering the first grid line precursor thereon can be 0.5s, 0.8s, 1s, 1.5s, 1.2s, 2s, 2.5s, 3s, 3.5s, 4s, 4.5s, or 5s.
[0094] Optionally, in step 105, the number of laser scans of a first gate line precursor is greater than or equal to 1 time, that is, the laser is scanned from one end to the other end of the first gate line precursor at least once, and laser sintering is performed once, and the laser is scanned from one end to the other end of the first gate line precursor at most 10 times, and laser sintering is performed 10 times, so that each position of each first gate line precursor is sintered as fully as possible to form a good electrical contact, and the number of laser sintering is not too many, so as to avoid unnecessary laser heat effects on the solar cell.
[0095] For example, the number of times the laser scans a first grid line precursor may be 1 time, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, or 10 times.
[0096] Optionally, the scanning speed of the laser on the first grid line precursor is 0.5m / s-100m / s. The greater the laser scanning speed, the greater the overlap of the laser spots. When the laser scanning speed is within this range, the overlap of the laser spots is more appropriate, which not only can fully sinter all positions of the first grid line precursor, but also can avoid unnecessary laser heat effects on the solar cell.
[0097] For example, the scanning speed of the laser on the first grid line precursor can be 0.5 m / s, 0.7 m / s, 1 m / s, 5 m / s, 20 m / s, 50 m / s, 100 m / s, 50.25 m / s, 60 m / s, or 80 m / s.
[0098] Optionally, the first electrode paste is an aluminum first electrode paste, the laser power used for sintering is a first power, and aluminum grid lines are obtained after sintering; the first electrode paste is a silver first electrode paste, the laser power used for sintering is a second power, and silver grid lines are obtained after sintering. The second power is greater than or equal to the first power. Specifically, the melting point of the aluminum first electrode paste may be lower than the melting point of the silver first electrode paste. Therefore, the aluminum first electrode paste is sintered with a relatively small power. The laser power is closely related to the characteristics of the first electrode paste. Not only can each first grid line precursor be fully sintered, but sintering with excessive power can also be avoided, thereby avoiding unnecessary laser heat effects on the solar cell.
[0099] For example, if an aluminum first electrode paste is disposed on one side of the first semiconductor layer, the aluminum first electrode paste can be sintered with a laser having a relatively low first laser power to obtain aluminum grid lines. For another example, if a silver first electrode paste is disposed on one side of the first semiconductor layer, the silver first electrode paste can be sintered with a laser having a relatively high second laser power to obtain silver grid lines. Thus, grid lines of different materials are fully sintered, resulting in a high-quality first grid line. This also avoids the problem of introducing excessive laser heat effects to the side where the aluminum first electrode paste is located, which would otherwise occur if grid lines of different materials were sintered at the same temperature. Furthermore, the first grid lines have a better contact effect and a low contact resistivity, further improving the performance of the solar cell.
[0100] Optionally, the second power is 10W (watts) to 1000W. At this power, the laser can fully sinter the silver first electrode paste, achieve excellent contact effects with the silver grid lines, and have low contact resistivity. For example, the second power here can be: 10W, 50W, 100W, 150W, 200W, 250W, 300W, 350W, 400W, 450W, 500W, 600W, 700W, 800W, 900W, or 1000W. The first power is 5W to 900W. At this power, the laser can fully sinter the aluminum first electrode paste, achieve excellent contact effects with the aluminum grid lines, and have low contact resistivity. For example, the first power can be 5W, 10W, 100W, 150W, 200W, 250W, 300W, 350W, 400W, 450W, 500W, 600W, 700W, 800W, or 900W. When selecting the first power and the second power, it is necessary to ensure that the first power is less than the second power. The specific values of the first power and the second power are not limited; for example, they can correspond to the optimal sintering temperature of the first electrode paste.
[0101] Optionally, before laser sintering, the method may further include: curing the first gate line precursor and the second gate line precursor. On the one hand, for the first gate line precursor, the curing can completely volatilize the organic matter in the slurry, thereby preventing the problem of uneven volatilization of the organic matter and poor sintering quality caused by direct laser sintering. This can further improve the laser sintering quality and may also appropriately reduce the power and number of scans during the laser sintering process. On the other hand, for the second gate line precursor, a second electrode is obtained by curing to form a good contact.
[0102] Optionally, the first gate line precursor and the second gate line precursor are cured at a temperature of 150°C to 300°C. Curing at a temperature of 150°C to 300°C will basically not bring thermal effects on the passivation performance of low-temperature film layers such as the second semiconductor layer and high-temperature film layers such as the first semiconductor layer, and will not reduce the passivation performance of the passivation film layer. This curing temperature range can allow the second gate line to form a good electrical contact without affecting the passivation performance of the film layer. In addition, the curing of the first gate line precursor here is completely different from the pre-sintering in the laser-assisted sintering of the prior art. The pre-sintering of the laser-assisted sintering requires a higher temperature so that the electrode burns through to form an ohmic contact, while the curing temperature of the present application is lower, which can allow the organic matter in the slurry to volatilize and does not cause the first gate line precursor to form an ohmic contact.
[0103] For example, curing may be performed at a temperature of 150°C, 170°C, 180°C, 200°C, 210°C, 250°C, 220°C, 225°C, 260°C, 290°C, or 300°C.
[0104] It should be noted that curing the second gateline precursor at a temperature of 150°C to 300°C allows the second gateline to form good electrical contact with the second semiconductor layer, eliminating the need for additional curing treatment. More specifically, the second electrode paste typically uses a low-melting-point binder phase such as epoxy resin, polyester resin, or acrylic resin. These materials melt or soften at relatively low temperatures to form good electrical contact. The first electrode paste herein often uses a high-melting-point binder phase such as glass powder. High-temperature sintering requires the binder phase to melt at a relatively high temperature, thus requiring a higher sintering temperature.
[0105] Optionally, before forming the first gridline precursor of the solar cell, a passivation anti-reflection layer may be formed on the first surface and the first semiconductor layer to enhance the passivation anti-reflection effect of the solar cell. The first gridline precursor is disposed on the passivation anti-reflection layer, and during laser sintering, the passivation anti-reflection layer can be burned through at the location where the first gridline precursor is disposed, thereby forming a metal-crystalline silicon alloy between the first gridline and the first semiconductor layer.
[0106] Optionally, before forming the second gate line precursor, a transparent conductive layer may be formed on the second semiconductor to cooperate with the second electrode paste sintered at a low temperature to improve the current collection capability. The second gate line precursor is disposed on the transparent conductive layer.
[0107] The present application also provides a solar cell, which is prepared by the aforementioned solar cell preparation method. The solar cell may include: a silicon substrate, the silicon substrate including: a first surface and a second surface relative to each other; a first semiconductor layer, located on the first surface of the silicon substrate; the first semiconductor layer has been subjected to a first temperature treatment; a second semiconductor layer, located on the second surface of the silicon substrate; the second semiconductor layer has been subjected to a second temperature treatment; the first temperature is greater than the second temperature, and the specific difference between the two is not limited. The first semiconductor layer and the second semiconductor layer have different doping types; a first gate line, located on the first semiconductor layer, with a metal-crystalline silicon alloy formed between the first gate line and the first semiconductor layer; and a second gate line, located on the second semiconductor layer.
[0108] Optionally, the line width of the first gate line is smaller than the line width of the second gate line. Specifically, the sintering temperature of the first gate line is higher, and the particle size of the metal conductive particles, such as silver particles, in the first gate line is smaller. Therefore, the first gate line can be set to be thinner or narrower, which not only reduces light blocking but also better matches the laser sintering process. The difference between the line width of the first gate line and the line width of the second gate line is not specifically limited here.
[0109] Optionally, the porosity of the first grid line is less than that of the second grid line. Specifically, the shape of the particles in the second grid line here is mainly spherical or sheet-shaped, which makes it easier to form voids. Therefore, the porosity of the second grid line is higher and the porosity of the first grid line is lower, so that the electrical connection effect between the first grid line and the first semiconductor layer is better and the conductivity is better. Moreover, in the subsequent process of forming a battery string, since the porosity in the first grid line of the present application is lower, the electrical connection between the first grid line and the conductive interconnection member such as the welding strip is also more reliable and firm, and the electrical performance of the formed battery string and photovoltaic module can be further improved. The difference between the porosity of the first grid line and the porosity of the second grid line is not specifically limited here.
[0110] Optionally, the solar cell further includes: a passivation anti-reflection film covering the first surface and the first semiconductor layer. For example, the passivation film and the anti-reflection film are stacked, and the passivation film is closer to the silicon substrate. For example, the passivation anti-reflection film can be an aluminum oxide passivation film and a silicon nitride anti-reflection film, covering the first surface and the first semiconductor layer, matching the aforementioned laser process, and providing a good passivation anti-reflection effect. The aluminum oxide passivation film here is closer to the first semiconductor layer or closer to the silicon substrate. The material of the passivation film can also be at least one of silicon oxide, aluminum oxide, and phosphorus silicon glass. The material of the anti-reflection film includes but is not limited to silicon nitride, silicon carbide, titanium oxide, etc.
[0111] The solar cell of the present application can be prepared by the aforementioned solar cell preparation method, and both can achieve the same or similar beneficial effects.
[0112] The present application also provides a photovoltaic assembly, comprising any of the aforementioned solar cells. The photovoltaic assembly may also include adhesive films located on both sides of the solar cells, without specific limitation. The photovoltaic assembly has the same or similar beneficial effects as any of the aforementioned solar cells, and relevant aspects may be referenced in conjunction with each other. To avoid repetition, the details will not be repeated here.
[0113] The present application is further explained below with reference to specific embodiments.
[0114] Example
[0115] The first step is to polish and clean the N-type single crystal silicon wafer to remove the damage caused by cutting the silicon wafer and obtain a silicon substrate.
[0116] In the second step, low-pressure chemical vapor deposition (LPCVD) is used to deposit a 1.2nm-2nm thick tunnel oxide layer (SiO) and an 80nm-150nm thick intrinsic polysilicon layer on the surface of the silicon substrate. Phosphorus diffusion is then used to form an N-type doped polysilicon layer. The square resistance after phosphorus diffusion is 60Ω / sq (ohms per square) to 100Ω / sq.
[0117] The third step is to deposit a 50nm-150nm thick silicon nitride mask layer on the first surface side of the silicon substrate using plasma vapor deposition, and then use a laser to groove the silicon nitride mask to achieve patterning. The first surface can be the light-facing side of the silicon substrate.
[0118] In the fourth step, a chain wet process equipment is used to use HF (hydrofluoric acid) to clean the PSG (phosphorus silicon glass) on the edge and the second surface side, and then the exposed polysilicon on the front is removed by a trough equipment, and the front is cleaned and textured at the same time.
[0119] The fifth step is to grow a 4nm-6nm aluminum oxide passivation film on the first surface side of the silicon substrate, and then deposit a 50nm-100nm silicon nitride anti-reflection film on the front side, and perform high temperature annealing.
[0120] In the sixth step, the oxide layer on the back side is cleaned using a chain device. Then, a 3nm to 30nm thick intrinsic amorphous silicon layer and an 8nm to 50nm thick P-type amorphous silicon layer are deposited on the second surface using PECVD. Finally, a 30nm to 100nm thick TCO (transparent conductive layer) is deposited on the second surface using physical vapor deposition (PVD). This second surface can be the backlight side.
[0121] In the seventh step, the first electrode paste on the first surface side is printed on the above-mentioned silicon substrate by screen printing to obtain a plurality of first grid line precursors, and the second electrode paste on the second surface side is printed by screen printing to obtain a plurality of second grid line precursors. The solar cell is then placed in an oven at 150°C-300°C for curing. The second electrode paste is cured to obtain the second grid line. Finally, the first electrode paste on the first surface side is subjected to high-temperature laser sintering using the laser sintering technology described in this application.
[0122] Figure 1 The laser sintering technology in this embodiment can be used. The laser 11 is an infrared continuous laser with a laser power of 10W-1000W. The laser scanning speed on the first grid line precursor is 0.5m / s-100m / s. In the direction of the line width of the first grid line precursor, the size of the laser spot is 110% of the line width of the first grid line precursor. The number of laser scans on a first grid line precursor is 1 to 10 times. Figure 1In the figure, 12 is the first gate line precursor on the first surface side, 13 is the second gate line on the second surface side, and the electrode pastes on the first and second surface sides are both silver electrode pastes. The silver electrode paste on the first surface side contains glass powder, while the silver electrode paste on the second surface side basically does not contain glass powder. Within the above parameter range, by adjusting parameters such as laser power, scanning speed, and number of laser scans, sintering process requirements at different temperatures can be achieved. Specifically, the silver electrode paste on the first surface side is laser sintered at a higher temperature. The silver electrode pastes on the first and second surface sides are both prepared by conventional screen printing silver paste methods. In this embodiment, the silver electrode paste used on the first surface side is a silver paste with added black dye. The main component of the black dye is an aromatic sodium sulfonic acid salt. The chromophore of the black dye includes at least one of: azo, anthraquinone triarylmethane, azine, oxathane, indigo, quinoline, phthalocyanine and nitroimide. The mass proportion of the black dye in the silver paste is 1.3%, and the mass proportion of the chromophore in the black dye of the silver paste is 35%. The black silver paste has excellent surface transmittance, reduces the reflection of the silver paste surface to the laser, fully absorbs the laser energy, and further converts it into the heat energy required for sintering the silver paste, reaching the melting temperature point required to form silver-silicon alloy points, and can be sintered quickly and accurately to achieve carrier collection and output without damaging the amorphous silicon film layer on the backlight side, thereby improving the performance of the solar cell.
[0123] Comparative Example
[0124] The only difference between the comparative example and the example is step 7. Specifically, in step 7 of the comparative example, no black dye is added to the silver electrode paste used on the first surface side. In the comparative example, a single sintering process at a high temperature of 800°C to 900°C is used to complete the metallization of the first and second surfaces. The remainder of the comparative example is identical to the corresponding example.
[0125] Under the same test conditions, the performance tests were conducted on the solar cells of the embodiment and the comparative example. The test results are shown in the following table.
[0126] Table: Performance comparison of solar cells of Examples and Comparative Examples
[0127]
[0128] From the table above, it can be concluded that compared with high temperature sintering furnace sintering, the front contact resistivity of the embodiment using laser sintering is lower, which is 0.1mΩcm lower. 2 , and the back contact resistivity is as low as 0.5mΩcm 2 , composite current density is as low as 2fA / cm 2, the passivation effect is better. Specifically, on the one hand, since the silver electrode paste on the first surface side contains black dye, combined with the laser sintering process, the sintering of the first gate line is more sufficient and the effect is better, so the resistivity of the first gate line is lower. On the second aspect, in the embodiment, the second gate line precursor only adopts the aforementioned low-temperature curing to form the second gate line, and the laser sintering process only sinters the silver electrode paste on the first surface side. Through the regulation of the laser process, the thermal impact on the intrinsic amorphous silicon layer and the doped amorphous silicon layer on the backlight side is extremely small, while the high-temperature sintering furnace used in the comparative example will destroy the passivation performance of the intrinsic amorphous silicon layer on the backlight side, etc. Therefore, in the embodiment, the resistivity of the second gate line is lower, and the composite current density of the battery of the embodiment is smaller. Specifically, Figure 2 is a SEM (scanning electron microscope) morphology image of the first gate line on the first surface side of the embodiment, Figure 3 The SEM morphology of the first grid line on the first surface side of the comparative example is shown by comparison. Figure 2 and Figure 3 Obviously, the first grid lines on the first surface side of the embodiment have fewer holes per unit area, and the holes are smaller in size. This is primarily due to the fact that, because the first electrode paste in the embodiment uses a silver paste containing a black dye, the laser energy is more concentrated, sintering is more complete, and fewer voids are formed after the silver paste melts. This improves the melting effect of the silver paste, resulting in better electrical contact with the first semiconductor layer and better conductivity. Furthermore, compared to the comparative example, which indiscriminately sintered both the metal contact area and the non-metal contact area of the solar cell at high temperature, the embodiment performs laser sintering primarily on the metal contact area, leaving the non-metal contact area largely unaffected by the high temperature. This allows the passivation performance of the passivation film layer in the non-metal area to essentially maintain its original performance, resulting in better passivation performance. Therefore, the solar cell in the embodiment has better passivation performance.
[0129] It should be noted that, in this document, the terms "comprises," "includes," or any other variations thereof are intended to encompass non-exclusive inclusion, such that a process, method, article, or apparatus comprising a series of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of other identical elements in the process, method, article, or apparatus comprising the element.
[0130] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are protected by the present invention.
Claims
1. A method for preparing a solar cell, characterized in that: include: Providing a silicon substrate, the silicon substrate comprising: a first surface and a second surface opposite to each other; forming a first semiconductor layer on the first surface; the first semiconductor layer undergoes a first temperature treatment; A second semiconductor layer is formed on the second surface; the second semiconductor layer is treated at a second temperature; the first temperature is greater than the second temperature; the first semiconductor layer and the second semiconductor layer have different doping types; Printing a first electrode paste on the first semiconductor layer to obtain a first gate line precursor, and printing a second electrode paste on the second semiconductor layer to obtain a second gate line precursor; Laser sintering is performed on the first grid line precursor to obtain the first grid line.
2. The method for preparing a solar cell according to claim 1, wherein: Before laser sintering, the method further comprises: The first gate line precursor and the second gate line precursor are cured.
3. The method for preparing a solar cell according to claim 2, wherein: The curing temperature is 150°C to 300°C.
4. The method for preparing a solar cell according to claim 1, wherein: In the direction of the line width of the first grid line precursor, the size of the laser spot is greater than or equal to the line width of the first grid line precursor and less than or equal to 120% of the line width of the first grid line precursor.
5. The method for preparing a solar cell according to claim 1, wherein: The first electrode paste is aluminum grid line paste, and the laser power used for sintering is a first power; the first electrode paste is silver grid line paste, and the laser power used for sintering is a second power; the second power is greater than or equal to the first power.
6. The method for preparing a solar cell according to claim 5, wherein: The second power is 10W-1000W; the first power is 5W-900W.
7. The method for preparing a solar cell according to claim 1, wherein: The first electrode slurry contains black dye; the mass proportion of the black dye in the first electrode slurry is 0.5% to 2%.
8. The method for preparing a solar cell according to any one of claims 1 to 7, characterized in that: forming a first semiconductor layer on the first surface, comprising: forming an entire first semiconductor layer on the first surface; The first semiconductor is patterned so that the first semiconductor layer partially covers the first surface.
9. A solar cell, characterized in that: include: A silicon substrate, comprising: a first surface and a second surface opposite to each other; a first semiconductor layer located on the first surface; the first semiconductor layer comprises a polysilicon layer; a second semiconductor layer located on the second surface; the second semiconductor layer comprises at least one of amorphous silicon, microcrystalline silicon, and nanocrystalline silicon; the first semiconductor layer and the second semiconductor layer have different doping types; a first gate line, located on the first semiconductor layer; a metal-crystalline silicon alloy is formed between the first gate line and the first semiconductor layer; The second gate line is located on the second semiconductor layer.
10. The solar cell according to claim 9, characterized in that The maximum size of a hole in a cross section of the first gate line is less than or equal to 2 micrometers.
11. The solar cell according to claim 9, wherein In the first gate line, a reflectivity of a surface facing away from the first semiconductor layer is less than or equal to 10%.
12. The solar cell according to claim 9, wherein The line width of the first gate line is smaller than the line width of the second gate line.
13. The solar cell according to claim 9, characterized in that The porosity of the first gate lines is smaller than the porosity of the second gate lines.
14. The solar cell according to claim 9, wherein The first grid line contains glass powder and black dye; the black dye also contains a color body; The mass proportion of the color body in the black dye is 10% to 60%.
15. The solar cell according to any one of claims 9 to 14, characterized in that: The first semiconductor layer includes: a tunneling oxide layer and a doped polysilicon layer stacked together, wherein the tunneling oxide layer is closer to the silicon substrate; The second semiconductor layer includes: an intrinsic amorphous silicon layer and a doped amorphous silicon layer that are stacked, wherein the intrinsic amorphous silicon layer is closer to the silicon substrate; and the doping type of the doped polysilicon layer is different from the doping type of the doped amorphous silicon layer.
16. The solar cell according to claim 15, characterized in that The solar cell further includes: a transparent conductive layer located between the second semiconductor layer and the second grid line; and / or, The first semiconductor layer partially covers the first surface; and / or, The solar cell further includes a passivation anti-reflection film covering the first surface and the first semiconductor layer.
17. A photovoltaic module, characterized in that: include: A solar cell prepared by the method for preparing a solar cell according to any one of claims 1 to 8, and / or a solar cell according to any one of claims 9 to 16.
Citation Information
Patent Citations
HBC solar cell
CN110061086A
Preparation method of solar cell
CN115939254A
Manufacturing method of solar cell, solar cell and photovoltaic module
CN116722079A
Preparation method of solar cell and solar cell
CN118039738A
Solar cell and manufacturing method therefor, and photovoltaic assembly
WO2024037167A1